2019
DOI: 10.3390/socsci8090253
|View full text |Cite
|
Sign up to set email alerts
|

Gender Inequalities in Early Career Trajectories and Parental Leaves: Evidence from a Nordic Welfare State

Abstract: Parental leaves are, besides unemployment, the main reason for career breaks in early career. Despite the progress in recent decades towards more equal sharing of childcare between mothers and fathers, the labour market risk due to parenting remains mainly with women. In this article, we analyse how parental leaves relate to early career trajectories of young Finnish men and women. Using longitudinal register data for 2005-2016 from the Finnish Centre for Pensions, we perform a multi-trajectory analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 31 publications
3
14
1
Order By: Relevance
“…For one thing, careers continue to remain gendered. In many industrial economies women's labor market participation is increasingly equal to men's, but even highly educated young women tend to have more fragmented careers, earn less than young men and take longer parental leaves (Aisenbrey & Fasang 2017;Kuitto et al 2019;Möhring 2016;Stawarz 2018). Along with unemployment, parental leaves are the main reason for early and mid-career breaks (Aisenbrey & Fasang 2017;Brückner & Mayer 2005;Kuitto et al 2019).…”
Section: Research Framework: Career Stability Versus Fragmentationmentioning
confidence: 99%
See 2 more Smart Citations
“…For one thing, careers continue to remain gendered. In many industrial economies women's labor market participation is increasingly equal to men's, but even highly educated young women tend to have more fragmented careers, earn less than young men and take longer parental leaves (Aisenbrey & Fasang 2017;Kuitto et al 2019;Möhring 2016;Stawarz 2018). Along with unemployment, parental leaves are the main reason for early and mid-career breaks (Aisenbrey & Fasang 2017;Brückner & Mayer 2005;Kuitto et al 2019).…”
Section: Research Framework: Career Stability Versus Fragmentationmentioning
confidence: 99%
“…In many industrial economies women's labor market participation is increasingly equal to men's, but even highly educated young women tend to have more fragmented careers, earn less than young men and take longer parental leaves (Aisenbrey & Fasang 2017;Kuitto et al 2019;Möhring 2016;Stawarz 2018). Along with unemployment, parental leaves are the main reason for early and mid-career breaks (Aisenbrey & Fasang 2017;Brückner & Mayer 2005;Kuitto et al 2019). After family formation, women often enter part-time jobs, switch industries, and are exposed to downward mobility and lower wages (Brückner & Mayer 2005;Buchmann et al 2010;Cech & Blair-Loy 2019;Stawarz 2018).…”
Section: Research Framework: Career Stability Versus Fragmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas female labour market participation has been almost on a par with men's participation rates since the 1980s, occupational segregation is higher than in many European countries and continues to lead to different labour market outcomes for men and women (European Commission, 2009;Gro ¨nlund et al, 2017;Lahtinen et al, 2020). Moreover, when compared to the situation for men, younger Finnish women's careers are more often interrupted for longer periods of time due to childbearing and care leaves, leading to considerably different outcomes in further careers (Kuitto et al, 2019). A low-rate cash-for-childcare system until the child is three years old serves as an incentive for mothers to interrupt their careers for longer time, especially among those in a weaker labour market position before motherhood.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, less than half of mothers whose youngest child was under three were in employment (Statistics Finland, 2017). Especially home care allowance has been linked to adverse labour market outcomes for women, including smaller earnings, stalled career development and lower accumulated pensions (Kuitto et al, 2019; Misra et al, 2011). Long leave for mothers contributes to the unequal division of labour as it strengthens traditional gendered division of domestic responsibilities (Hook, 2010) whereas research has shown that fathers taking longer leave are likelier to reduce their working hours and increase childcare and household work (Bünning, 2015).…”
Section: Struggles Over Family Leave Policy In the Finnish Corporatist Contextmentioning
confidence: 99%